2021
DOI: 10.1177/17423953211067435
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based patient classification system for adults with stroke: A systematic review

Abstract: Objective To evaluate the existing evidence of a machine learning-based classification system that stratifies patients with stroke. Methods The authors carried out a systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations for a review article. PubMed, MEDLINE, Web of Science, and CINAHL Plus Full Text were searched from January 2015 to February 2021. Results There are twelve studies included in this systematic review. Fifteen algorithms were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…The features are one of the essential combinations of a model as it demonstrates the correlation of the target variable of a model and attributes the appropriate of the model’s predictions and performance. 11 Overall, in nine included studies, a total of seven main features were included. Notably, one study can report using more than one feature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The features are one of the essential combinations of a model as it demonstrates the correlation of the target variable of a model and attributes the appropriate of the model’s predictions and performance. 11 Overall, in nine included studies, a total of seven main features were included. Notably, one study can report using more than one feature.…”
Section: Resultsmentioning
confidence: 99%
“… 10 In light of ischemic stroke diagnosis, multiple types of ML have shown effectiveness in detecting ischemic stroke among adults. 11 One of the promising and powerful methods is neural networks, also known as artificial neural networks or simulated neural networks, which are a class of algorithms loosely modeled on connections between neurons in the brain. 12 As is evident from previous studies, the use of the neural networks algorithm is shown to improve the accuracy of several medical diagnoses, including cancer diseases such as lung cancer, skin cancer, and gastric cancer, or even time-sensitive diseases, such as coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the following ve machine learning algorithm models were constructed as follows: Support Vector Machine (SVM) [42] , k Nearest Neighbour (KNN) [43] , Random Forest (RF) [44] . Decision tree (TREE) [45] .…”
Section: Machine Learningmentioning
confidence: 99%
“…The result found that machine learning models have the potential to help healthcare providers with stroke diagnoses that can lead to early treatment and improve patient outcomes. 7 …”
Section: Introductionmentioning
confidence: 99%